Artistic Research Creation for Publicly Engaged Scholarship. Issue 1 (27th February 2019) - Bath, Jon
In this paper I discuss the adoption of artistic research creation methodologies, the creation and exhibition of artistic works closely aligned with scholarly research, as a way to increase public engagement with academic research. I begin by discussing the need for scholars to consider the 'public first' when developing research communication plans, and draw upon the emergence of 'mobile first' interface design as a metaphor. With mobile first development, also known as progressive enhancement, 'You start by establishing a basic level of user experience that all browsers will be able to provide when rendering your web site, ' but you also build in more advanced functionality that will automatically be available to devices, such as desktop computers (W3C 2015 ). I argue that we need to prioritize public first research outputs if we are truly serious about engaging the public in our research. I then move into a discussion of various research creation methodologies and explain how they are similar to, and differ from, critical making, another emergent humanities research practice that is based upon the making of physical objects. Finally I provide examples of successful research creation activities, including some related to my current SSHRC-funded project, The Post-Digital Book Arts.